The Vanishing Farmland Crisis Critical Views of the Movement to Preserve Agricultural Land - Baden, John (Book collections on Project MUSE., 1985)
The 1979 publication Where Have All the Farmlands Gone? by the National Agricultural Lands Study painted a bleak future for American farmlands. Threatened by encroaching construction and soil erosion, these lands were seen as endangered--and as the direct prelude to a nationwide shortage of both food and fiber. The NALS report, to which eleven federal agencies contributed, argued that landuse planning and control must be employed to protect valuable farmland from "urban sprawl." First published in 1984, this collection of essays by a distinguished group of economists, including Theodore W. Schultz, Julian L. Simon, and Pierre Crosson, takes issue with the belief that croplands need governmental protection. Rather, the collection as a whole supports two theses: 1) shrinking farm acreage is not a serious problem, and 2) individual choices by landowners in a free market setting result in betterorganized land use than would governmental landuse planning and regulation.